Relatório crítico-reflexivo sobre a pesquisa de in(ter)venção-ação : concepções políticas e pedagógicas da escola do campo. - (:unkn) unknown (Universidade Federal do Pampa, 2016)
This work presents the results of in(ter)vention-action research executed by the school community of Atanagildo Domingues School in Arroio Grande –RS. In order to discuss the education that is being offered to the sons and daughters of workers belonging the community in which the school operates. This school is geographically situated in the countryside, so we adopted, as a reference, to discuss the concept of education that underpins the school's educational project, the conceptions of the Rural Education. This research was performed based on the principles of actionresearch, anin(ter)vention research action which had the role of the subjects that make up the school community Atanagildo Domingues. So, families, teachers, students and all staff were present to discuss, interact, discuss and participate in the process of understanding and ownership of the educational of the school project. They were held discussion circles constructed from the Freirian inspiration, the Culture Circles. The study theoretical foundation was the law that legitimizes the Field of Education created from the struggles of social movements. There were four decisive moments entitled Discussion circles. The first circle was called Pilot Circle. In this space the community had the opportunity to build strategies and define content for the realization of discussion circles. In this way, they understood that to build their ideal is necessary that the school educates in a libertarian perspective. This synthesis emerge the themes of the second and third circles that was: Liberating Education, one that builds the way to transformation. Multiplying the knowledge was the subject of the fourth circle. And in this of knowledge multiplication perspective, the subjects still actively exchanging knowledge with a mounted agenda workshops where everyone has the opportunity to socialize what knows, keeping an approximation mechanism with school and producing new syntheses, in collective that intends to solidify. We conclude that through in(ter)vention-action was possible to establish affective, social, cognitive and political ties with the school community searched School. The walk that drew to school that dreams must continue to be walked.
Keywords: Educação no campo; Educação rural; Intervenção; Legislação; CNPQ::CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO::EDUCACAO RURAL